Pengaruh Pemberian Pisang Ambon (Musa Paradisiaca S) Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi - Hepti Muliyati (Jurnal Keperawatan Muhammadiyah, 2017)
Objective: to analys the effect of Ambon banana administering (Musa Paradisiaca S) toward reducing of blood pressure of elderly in hypertension. Methods: This article is quatitative research with pre experiment design (pre and post test without control). The population of this research is all the elderly who live in Social House of Tresna Werda Al Kautsar Foundation, Palu. The number of sample was 6 elderly and taken by total sampling technique that done from 1 to 7 August 2017. Statistict test by wilcoxon signed test. Results: T h e result of this research shown that have decreasing of Blood Pressure after giving therapy of Ambon Banana about 3 pieces (303 gram) a day within one week.Decreasingofsystolepressureabout 25 mmHg and diastole pressure 13,34 mmHg with p value = 0,023 (p<0,05). Conclusion: Administering of Ambon banana have effect toward decreasing of blood pressurefor elderly in Hypertension at Social House of Tresna Werda Al Kautsar Foundation, Palu